Final environmental impact statement : wilderness recommendation : Gates of the Arctic National Park and Preserve, Alaska. - United States. National Park Service. Alaska Regional Office. ([Anchorage, Alaska : Alaska Regional Office, National Park Service, 1988)
"NPS D-15A"--P. [264]. Includes index. "August 1988"--P. [264]. Shipping list no.: 88-515-P. Cover title. Bibliography: p. 254-260. Mode of access: Internet.